The influence of multiple-deviation coefficient n to paramatric generating regions N=3,5,7 - Nguyen, Binh Vu Cam; Vo, Ha Ly Thanh; Nguyen, Lam Dang; Do, Nguyet Thi Minh; Vu, Phi Anh (VNU Journal of Science: Mathematics - Physics; Vol 20 No 3AP, 2017)
Abstracts